Identification of Gas Sand Horizons of the Rashidpur Structure, Surma Basin, Bangladesh, Using 2D Seismic Interpretation - Abu Reza Md. Towfiqul Islam; Md. Ahosan Habib (International Journal of Geophysics)
A total of 13 seismic sections were used for 2D seismic interpretation in order to assess the subsurface geometry of gas sand horizons and hydrocarbon prospect of the Rashidpur structure, Surma Basin, Bangladesh. Out of five reflectors, two selected reflectors were mapped for the study. The top of the Upper Gas Sand (R3) reflector was elongated in N-S with the axis swinging slightly to the east on the northern plunge. North-South trending thrust fault was identified in the eastern part which is parallel to the axial line of the structure. The reflection patterns of the gas sand horizons were parallel to each other and similar in nature. The reflection coefficients were positive at the base and negative at the top of the each gas sand horizons. Velocity dropped from 2562 m/s to 2177 m/s in the Upper Gas Sand (R3) and 4320 m/s to 3413 m/s in the Lower Gas Sand (R5) reflector. Bright spot and amplitude anomalies were identified on the top of the both gas sand horizons. The result depicts that the shape of the gas sand horizons is asymmetric anticline. The structure is compressed and elongated NNW-SSE trending anticline. The study reveals hydrocarbon potentiality of the structure.